Factores de riesgo asociados a la recurrencia de preeclampsia en gestantes del servicio de alto riesgo obstétrico del Hospital Nacional Guillermo Almenara Irigoyen en el 2017 - 2018 - Villanueva-Bustamante, Jesús M. (2020)
Objective: To determine the risk factors associated with the recurrence of preeclampsia in the HNGAI of 2017-2018.Methods: This is an observational, retrospective, analytical case-control study where descriptive and cross tables were used for the OR.  Results: After the univariate analysis of the risk factors, the highest prevalence of pregnant women between 20 and 35 years of age was seen, with a figure of 59.4%. After bivariate analysis, an association was observed between the variable overweight or obesity and the recurrence of preeclampsia with a p value of 0.031 and an OR of 1.94 (1.05 - 3.56) with 95% CI. An association was also seen between housewife and recurrence of preeclampsia with a p value of 0.030 and an OR of 1.95 (1.06 - 3.58) with a 95% CI. Finally, in the multivariate analysis, the factors studied maintained obesity with a p value of 0.036 and an adjusted OR of 1.99 (1.04- 3.79) at the 95% CI and the occupation variable a p of 0.023 and an adjusted OR of 2.07 (1.10 - 3.90) with a 95% CI. Conclusions: It is concluded that the variables overweight or obesity and occupation, in this case being housewives, is associated with recurrence of preeclampsia.